Optimization of algoflora of sod-podzolic sand soil in the conditions of its cultivation - Gaevskii, Eugene E.; Kulikov, Yaroslav K. (Experimental Biology and Biotechnology, 2019)
As a result of studies of the taxonomic composition and quantitative development of soil algae on sod-podzolic sandy soil of varying degrees of optimization 45 species of soil algae were identified that belong mainly to four divisions: Chlorophyta, Cyanophyta, Bacillariophyta, Xanthophyta. Also in the soil were found not numerous representatives of divisions Euglenophyta and Rhodophyta. Different departments are represented unequally. Most of the found representatives we edaphophilic algae, the participation of hydrophilic algae in the formation of algogroups at the studied sites was insignificant (represented by one species of Cosmarium undulatum var. minutum Wittr.). No amphibial algae were found. The species composition and the spectrum of life forms in different versions of the experiment varied. The control variant of the experiment was represented by the smallest number of species; there are also no nitrogen-fixing cyanobacteria in the soil.